Two‐layer coordination architecture HIF detection with µPMU data. Issue 15 (31st August 2018) - Wang, Xiaojun; Zhang, Yongjie; Luo, Yiping; He, Jinghan; Ling, Ping; Fang, Chen
Abstract : The detection of high‐impedance fault (HIF) on distribution network has been one of the most difficult problems. This study presents a data‐driven method for HIF detection by using single‐ended micro‐phasor measurement unit (µPMU). This approach is based on the two‐layer coordination architecture, local side with μPMUs and master station for further analysis. At the local side, the μPMUs gather the synchronous data and achieve feature extraction with k ‐means clustering algorithm and principal component analysis. For determining the amounts of data categories, the authors adopt a method based on silhouette coefficient. Meanwhile, send the characteristics to the master station, then detect the HIF fault through the support vector machine. Finally, the method was tested on a 34 nodes distribution network in PSCAD/EMTDC. The results justify the effectiveness and the proposed detection scheme has >85% accuracy.